The Effects of Hypoxia on U937 Cell Line in Mesenchymal Stem Cells Co-Culture System - Mostafa Ejtehadifar; Karim Shamsasenjan; Parvin Akbarzadehlaleh; Sarah Zahedi; Narjes Kazemi (Tabriz University of Medical Sciences, 2016)
Purpose: Mesenchymal Stem Cells (MSCs) are the most important members of Bone Marrow (BM) milieu. MSCs affect different kinds of cells, particularly malignant cells of hematologic malignancies, but the effects of MSCs are unclear exactly. Here we analyzed the effects of derived Umbilical Cord Blood-MSCs on proliferation, cell death and some surface markers of U937 cell line in a Co-culture system with MSCs. Methods: Here we designed Co-culture systems as a model of BM milieu. We cultured U937 cells on UCB-MSCs and MSCs Conditioned Medium (C.M) driven and then treated U937 cells with optimum concentration of chloride cobalt (CoCl2) as a hypoxia-mimetic agent. In addition, we applied suitable concentrations of H2O2 to induce cell death. Proliferation rate, cell death rate and some surface markers of hypoxic U937 cells were analyzed by MTT assay, flow cytometry and Real Time-PCR were flown respectively. Results: UCB-MSCs showed supportive effects on U937 proliferation rate in normoxia and hypoxia. Lethal effect of H2O2 suppressed in the presence of UCB-MSCs in hypoxia and normoxia. Among CD11a, CD14, CD49d, CD54 and CD116 markers, CD49d was down regulated in presence of UCB-MSCs and CD116 was up regulated in hypoxia. Other markers didn't show any significant changes. Conclusion: This work provides evidences that MSCs play critical roles in U937 cells biology. These observations shed new light on MSCs roles and demonstrated that MSCs should be regarded as an important member of BM milieu in several clinical applications such as BM transplantation prognosis and treatment of hematologic malignancies.